Spatiotemporal expression of endogenous TLR4 ligands leads to inflammation and bone erosion in mouse collagen‐induced arthritis. Issue 11 (6th September 2016) - Kiyeko, Gaëlle Wambiekele; Hatterer, Eric; Herren, Suzanne; Di Ceglie, Irene; van Lent, Peter L.; Reith, Walter; Kosco‐Vilbois, Marie; Ferlin, Walter; Shang, Limin
Abstract : The initial immunization with Collagen II (CII) and CFA induces Tenascin‐C release and TLR4 activation. TLR4 activation on macrophages and osteoclasts promotes joint inflammation and bone erosion. Joint inflammation and damage increase the production of numerous endogenous TLR4 ligands (immune complexes containing citrullinated fibrinogen (cFb‐IC), Tenascin‐C, S100A8/A9, and HMGB1). Endogenous TLR4 ligands promote joint damage, sustaining disease progression. Abstract : Increased expression of endogenous Toll‐like receptor 4 (TLR4) ligands (e.g., Tenascin‐C, S100A8/A9, citrullinated fibrinogen (cFb) immune complexes) has been observed in patients with rheumatoid arthritis (RA). However, their roles in RA pathogenesis are not well understood. Here, we investigated the expression kinetics and role of endogenous TLR4 ligands in the murine model of collagen‐induced arthritis (CIA). Tenascin‐C was upregulated in blood early in CIA, and correlated positively with the clinical score at day 56. Levels of S100A8/A9 increased starting from day 28, peaking at day 42, and correlated positively with joint inflammation. Levels of anti‐cFb antibodies increased during the late phase of CIA and correlated positively with both joint inflammation and cartilage damage. Blockade of TLR4 activation at the time of the first TLR4 ligand upregulation prevented clinical and histological signs of arthritis. A TLR4‐dependent role was also observed for Tenascin‐C and cFb immune complexes in osteoclast differentiation in vitro. Taken together, our data suggests that the pathogenic contribution of TLR4 in promoting joint inflammation and bone erosion during CIA occurs via various TLR4 ligands arising at different stages of disease. The data also suggests that Blockade of TLR4 with monoclonal antibodies is a promising strategy in RA treatment.